UJI PREFERENSI MAYARAKAT LOKAL TERHADAP NASI DARI VARIETAS PADI INPARI 7, INPARI 8 DAN INPARA 2 - Untari Untari; Ineke Nursih Widyantari (AGRICOLA, 2013)
Every region in Indonesia has a diversity of rice varieties produced and sensory quality is the most important thing noticed by consumers rice is considered by most consumers, even the public preference for rice growing. Purpose of this  research is to identify the preferences of local residents who live in the district of Merauke on rice varieties Inpari 7, 8 and Inpara 2 is being developed in Merauke. The experiment was conducted in a local village is Kampung Urumb, Waninggap Nanggo and Kampung Matara, research activities will be carried out over the past two months are September and October 2012. The main material used in this study were rice varieties Inpari 7, 8 and Inpara Inpari 2. The equipment used to support these activities, among others, such as cooking utensils, rice cooker, stir rice, plates, spoons, rice box, plastic pots. Research data will be analyzed by tabulation, data tabulation done by  data grouping according to the type of data that was obtained in the execution of the test data retrieval level of preference (preference) of processed rice into rice using hedonic test and rank test. The results of the study by using hedonic test and rank test can be concluded that 1) Aroma rice varieties Impara 2 (score of 2.17) than the most preferred local varieties aroma Inpari 8 (score 1.91) and 7 (score of 1.78). 2) Sense of rice varieties Impara 2 (score of 2.35) than the most preferred rice varieties taste Inpari 7 (score 1.96), and Inpari 8 (score 1.87). 3) Variety Impara 2 has ranked first through overal assessment using next rank test followed by Inpari 7 and 8 with the sequence of each percentage is 52%, 26% and 22%.